Utilization of palliative care services for cardiac arrest patients undergoing therapeutic hypothermia: A retrospective analysis. (March 2017) - Zern, Emily K.; Young, Michael N.; Triana, Taylor; Xu, Meng; Holmes, Benjamin; Borges, Nyal; McPherson, John A.; Karlekar, Mohana B.
Abstract: Background: Palliative care (PC) services are integral to the care of patients with advanced medical illnesses. Given the significant morbidity and mortality associated with cardiac arrest, we sought to measure the use and impact of PC in the care of patients treated with therapeutic hypothermia (TH). Methods: We conducted a retrospective study of 317 consecutive patients undergoing TH after cardiac arrest. We compared intensive care unit (ICU) characteristics and clinical outcomes of subjects who received PC consultation (n = 125) to those who did not (n = 192). Results: The proportion of TH patients with PC consultations increased to greater than 60% by 2013, corresponding to our institution's expansion of PC services, development of a dedicated PC unit, and integration of this service into our published TH protocol. In the TH population, time to return of spontaneous circulation (ROSC) was associated with higher inpatient mortality (p < 0.001) and placement of a PC consult (p = 0.011). TH patients who received PC consultation had longer ICU stays (p = 0.034), more ventilator days (p < 0.001), and higher inpatient mortality (p < 0.001). When these measures were analyzed cohort-wide comparing all TH patients pre- and post-2013, at which time the frequency of PC consultation had dramatically increased, there were no statistically significant differences in ICU care or outcomes. Conclusion: In our population of cardiac arrest patients undergoing TH, the utilization of PC services has increased over time, particularly for those patients with high morbidity and mortality. Future randomized studies may further delineate optimal patient selection for PC consultation to better facilitate goals of care discussions and timely medical decision-making.